Pengabdian Masyarakat Desa Budaya Lingga Kecamatan Simpang Empat Kabupaten Karo - Maisaro, Najiyah; Siregar, Susilawati; Fadilah, Nurhikmah; Ritonga, Elfi Yanti; Simamora, Irma Yusriani; Aulia, Fadlan; Walid, Muhammad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Community service is a manifestation of the duties of lecturers and students in carrying out the third Tri Dharma of Higher Education, namely Community Service. Through community service activities carried out in Lingga Cultural Village, Simpang Empat District, Karo Regency, there is a synergy between universities and the community as a form of mutual tolerance and socialization. The purpose of this service is to embrace the community in socializing and also uphold religious meaning in the life of Muslim minority communities. Community service is carried out through socialization activities with the village community, carrying out various kinds of competitions, mutual cooperation and teaching activities. The results of the service provide an illustration of increasing enthusiasm and increasing understanding of the community, especially teachers and parents about religious tolerance and also socializing with each other without distinguishing race, ethnicity, religion from one anither. Keywords: devotion, Simpang Empat sub-district